STUDI TOKOH SYEKH MUHAMMAD ARSYAD AL-BANJARI (1710-1812) ATAS POLEMIK ARAH KIBLAT DI BATAVIA PADA MASA HINDIA BELANDA - Nur Aisyah, Nur Aisyah; Suriyadi; Nur Hidayat (ELFALAKY: Jurnal Ilmu Falak, 2023)
Qibla direction is an important issue for Muslims, because facing the Qibla is one of the conditions for the validity of prayer. Scholars agree on the obligation to face the Qiblah. However, they differed in terms of whether what was demanded should be facing the ainul ka'bah (the building) or was it just the direction. In the 12th century H, the famous figure of the Shafi'i School at that time was Sheikh Muhammad bin Sulaiman al-Kurdi (1127-1194 H). He was the main teacher of Sheikh Muhammad Arsyad al-Banjari in the field of fiqh. In 1772 M, when Sheikh Muhammad Arsyad al-Banjari and his three friends returned from Haramain and then stopped by Batavia, he saw the mihrabs there were not facing the Kaaba . He argued that the mihrab should be aligned with the qibla by shifting 25 degrees to the right or north. At that time Sheikh Arsyad changed the Qibla of one of the mosques in Batavia, and then a commotion arose in the people of Jakarta, and received a letter of rebuttal from a sheikh of the congregation at that time Sheikh Abdullah bin Abdul Qohhar al-Jawi. This conflict involved the Governor General of the Dutch East Indies Petrus Albertus van der Parra (1761-1775) and a priest who was an astronomer Johann Mauritz Mohr (1716-1775). And in the end, Sheikh Arsyad's argument was accepted by all parties and the conflict ended peacefully, as documented in his story in the treatise "Mas-alatul Qiblah fil Batawi" written by Sheikh Muhammad Arsyad al-Banjari in 1772 M.